Testing of a synthetic phonics-based targeted reading intervention for students with reading difficulties in Year 1: protocol for an efficacy randomised controlled trial - Jon Quach; Janet Clinton; Georgia Dawson; Libby Smith; Tanya Serry; Sharon Goldfeld (BMJ Publishing Group, 2018)
Introduction Literacy is fundamental for educational achievement, and in the longer term contributes substantially to a range of life skills. Literacy difficulties during the early years of school are associated with long-term impacts on academic success, with differences in academic achievement sustained through children's schooling. Therefore, addressing literacy difficulties during the early years of school is essential in reducing the risk of children progressing onto negative academic, psychosocial and vocational trajectories. This trial will determine whether a phonics-based reading intervention can improve the reading comprehension of students identified as low-progress readers in the second year of primary school.Methods/design We recruited 236 students fromnine schools after screening for reading difficulties in the second year of primary school (Year 1). Schools in Sydney and Central Coast of New South Wales will be invited to participate via an opt-out consent process. All children identified as being in the bottom 25th percentile using the Wheldall Assessment of Reading Lists will be eligible for the trial. These children will be randomised into either 'usual teaching' or 'intervention' groups. Trained school support teachers will deliver the MiniLit intervention. Intervention: In groups of four, children will complete a daily 1-hour lesson with their MiniLit teacher over 20 school weeks. Follow-up: Immediately after intervention completion and 6 months later using child face-to-face assessments. Primary outcome: Reading comprehension at 6 months after intervention completion. The study will have an embedded process and cost-effectiveness evaluation.Discussion The Building Better Readers trial will be the first efficacy randomised controlled trial comparing usual teaching with a phonics-based reading intervention for children with reading difficulties in Year 1 of primary school in Australia. The randomised design will limit the effect of bias on outcomes seen in other studies.Trial registration number ACTRN12617000179336